2020
DOI: 10.21037/apm-20-887
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of coronavirus disease 2019 in Gansu province, China

Abstract: Background: The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has outbreak in the world. Little is known about the clinical characteristics of patients with SARS-CoV-2 infection in the high-altitude region of China. We reported the clinical characteristics of patients with coronavirus disease 2019 in Gansu province, China.Methods: In this retrospective study, patients with laboratory-confirmed SARS-CoV-2 infection were consecutively enrolled from January 21, 2020 to February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 14 publications
2
44
0
2
Order By: Relevance
“…As a sign of worse disease progression, patients show leukopenia and lymphopenia (Guan et al, 2020; Yue et al, 2020). Chest computed tomography scans (CTs) of some patients with SARS‐CoV‐2 infection show bilateral pneumonia (Du et al, 2020; Guan et al, 2020; Wang, Yin, et al, 2020; Yue et al, 2020). Pneumonia is a common clinical manifestation of the COVID‐19 and can lead to acute respiratory distress syndrome (ARDS).…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…As a sign of worse disease progression, patients show leukopenia and lymphopenia (Guan et al, 2020; Yue et al, 2020). Chest computed tomography scans (CTs) of some patients with SARS‐CoV‐2 infection show bilateral pneumonia (Du et al, 2020; Guan et al, 2020; Wang, Yin, et al, 2020; Yue et al, 2020). Pneumonia is a common clinical manifestation of the COVID‐19 and can lead to acute respiratory distress syndrome (ARDS).…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…The characteristics of both the viruses in terms of epidemiological and clinical presentation are shown in Table 2 [ 8 ]. A study by Yue et al showed a huge overlap between clinical spectrums of both diseases, with fever and headache being the most common symptoms in both [ 2 ]. Our patient had presented with fever and bleeding manifestation with no respiratory and cardiovascular symptoms at presentation or no exposure to COVID-19, and hence the possibility for a tropical illness was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in a lethal global pandemic [ 1 ]. It exhibits varied clinical manifestations, potentially affecting every organ system, although fever remains a common symptom [ 2 ]. In India, dengue virus (DENV) infection, transmitted by Aedes aegypti , is one of the most common causes of acute undifferentiated febrile illness (AUFI) with endemicity, usually during the monsoon and post-monsoon seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Available data from Chinese studies indicate that chronic liver diseases can be diagnosed in 2–11% of subjects with COVID-19 [ 11 17 ]. In Italy, Grasselli et al [ 18 ] reported that among 1591 patients in intensive care units in the Lombardy region, 3% had a history of liver disease.…”
Section: Cirrhosis and Covid-19mentioning
confidence: 99%